First patellar dislocation: from conservative treatment to return to sport - Respizzi, Stefano; Cavallin, Ramon (Joints, 2014)
Treatment of first patellar dislocation is usually conservative and the subsequent rehabilitation program is based on specifically formulated objectives, which can be divided into different stages: stage 1: resolution of pain, swelling and inflammation; stage 2: recovery of joint motion and flexibility; stage 3: recovery of muscle strength; stage 4: recovery of motor patterns and coordination; and stage 5: recovery of the sportspecific athletic action and return to sporting activity. The aim, in the management of a patient affected by first patellar dislocation, is to achieve the best possible functional recovery: since this is a condition often affecting young athletes, this means returning them to their pre-injury conditions, both in terms of fitness and the level of sporting activity practiced. By proceeding through functional stages, the risk of recurrence of the dislocation can be reduced. The “go-ahead” to resume sporting activity can only be given in the presence of normal results on sport-specific functional tests.
Keywords: athlete; dislocation; patella; rehabilitation; sport